The Ability of biofilter sponge demospongiae class with various forms of growth towards the turbidity and total suspended solid - Soeid, Marini; Haris, Abdul; Syafiuddin, Syafiuddin (Hasanuddin University, 2019)
The sponge is an invertebrate animal from phylum porifera that lives permanently and filters out what is in the water column. The sponge has various forms of growth, including massive, branching, and submissive. Each form of growth is indicated to have different filtering abilities, so this research needs to be done. This study aims to determine whether the ability to filter (biofilter) Turbidity and Total Suspended Solid sponge depends on the form of growth (Massive, Submassive, and Branching). This research was conducted from September to October 2016. Taking sponges in the waters of Barranglompo Island, testing was carried out at the Hatchery Marine Station at Hasanuddin University, Barranglompo Island and measurements of water quality parameters were carried out at the Chemical Oceanography Laboratory, Department of Marine Sciences, Faculty of Marine and Fisheries, Hasanuddin University. The acclimatization process needs to be done to adapt the sponge before being given treatment. Each aquarium is filled with seawater that has been mixed with sediments as much as 0.17 mg/l. Then each form of sponge growth is put into an aquarium with the same body volume of 500 cm3 and sees the ability to filter it for 10 hours and 24 hours. After that, water samples were taken at each aquarium to measure turbidity parameters, Total Suspended Solid, and Total Organic Materials. The results showed that at 10 hours and 24 hours the sponge with submassive growth forms filtered more particles in the water column than massive and branching growth forms, while sponge with branching growth forms run into stress and death after filtering for 24 hours.Keywords: growth pattern, biofilter, sediment, sponge.